Implementation Of Combined Administration Practices In The Quality Of Public Service In The Property Of The City Of South Jakarta - Hanafi, Muhammad Nur; Saepudin, Aep; Suryaman, Warman (Program Pascasarjana STIE Amkop Makassar, 2023)
The purpose of this study is to describe the stages of implementing administrative service policies in Jatipadang Village according to the factors that influence the implementation of administrative service policies in Jatipadang Village. By using a qualitative descriptive method, this study produced several conclusions: The socialization that was carried out between the city government and Kelurahan was not completely evenly distributed and did not raise public awareness. The quality and quantity of equipment is inadequate and there is insufficient coordination between the relevant authorities. The interests of both parties concern the village in particular. Based on the results of the research analysis, Kelurahan plays an important role as a community-based service center, especially in large and hard-to- reach areas. Complainants must not only have comprehensive authority according to their role, but must also have adequate resources, infrastructure and equipment both quantitatively and qualitatively. Keywoard: policy implementation, delegation of authority, administrative service policy